Taking Risk: Interactions and Implications - Rudi Zulfikar (FEB Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to provide empirical evidence about the influence of Independent Commissioners, Audit Committee and Risk Monitoring Committees on Risk Taking moderated by Charter Value in the Indonesian banking industry. Risk Taking is a policy-making by management that contains risks in its decisions.This research was conducted by analyzing the influence of the Independent Commissioners, the Audit Committee and the Risk Monitoring Committee. In this case, the institutions are the organs of the Board of Commissioners and their instruments of Risk Taking. The population of this study is the entire banking industry listed on the Indonesia Stock Exchange from 2018 to 2021. The sampling technique using purposive sampling resulted in 127 observations. The data analysis method used to test the hypothesis in this study is Moderate Regression Analysis (MRA).The study results indicate that the Independent Commissioner, Audit Committee and Risk Monitoring Committee are factors that monitor management to reduce risk in managing companies in the banking industry. This shows that the monitoring carried out by the Independent Commissioner, the Audit Committee, and the Risk Oversight Committee is an effective mechanism for reducing risk. Other results, the interaction of Charter Value with Independent Commissioners and the Risk Monitoring Committee, cannot be proven, while the interaction between Charter Value and the audit Committee functions as a moderator. Furthermore, the results of this study also prove that reducing risk-taking will improve financial performance.